Integrating Indigenous Balinese Hindu Values into Digital Persuasive Tax Communication: The LV-DPC Model from the E-Palapa Platform in Badung Regency, Indonesia - I Made Deddy Sandrawan; I Nyoman Linggih; I Nyoman Kiriana (Smart Society, 2026)
Background: Although digital tax administration has improved public revenue management, little is known about how indigenous cultural values shape persuasive communication in e-government. Methods: This study adopted an interpretive qualitative case study at the Badung Regency Revenue Agency, Indonesia. Data were gathered through in-depth interviews, participant observation, and document analysis involving government officials and taxpayers from corporate, individual, and MSME sectors. Findings: The analysis shows that E-Palapa combines central and peripheral persuasion processes that are reinforced by Tri Hita Karana, Tat Tvam Asi, and Menyama Braya. It also reveals User-Initiated Blended-Channel Communication and persuasion-induced financial harm among financially vulnerable MSMEs, highlighting the diverse consequences of digital persuasive communication. Conclusion: The integration of indigenous values enriches persuasive digital tax communication by strengthening trust, voluntary compliance, and citizen engagement. Novelty/Originality of this article: This study introduces the Local Value-based Digital Persuasive Communication (LV-DPC) Model, providing a culturally grounded framework that extends persuasive communication theory within digital taxation and e-government.